Plasma exchange followed by convalescent plasma transfusion in COVID-19 patients. (August 2021) - Roshandel, Elham; Sankanian, Ghazaleh; Salimi, Maryam; Jalili, Arsalan; Salari, Sina; Sadeghi, Amir; Hashemian, Seyed Mohammadreza; Moshari, Mohammad Reza; Pirsalehi, Ali; Hajifathali, Abbas
Highlights: One of the potential treatments in newly found infectious disease is plasma exchange (PE) with convalescent plasma (CP). CRP, LDH, AST, BUN, BilT, D, D-dimer, IL-6 and CD4+/CD8+ T cells after PE and continued to improve of COVID-19 patients'. PE/CP reduce acute inflammation led to a considerable improvement in patients' clinical features of COVID-19. Abstract: Background: Coronavirus disease 2019 (COVID-19) is an emerged pandemic disease with no specific treatment. One of the potential treatments in newly found infectious disease is plasma exchange (PE) with convalescent plasma transfusion (CPT). This case series aimed to evaluate the primary PE and CPT in five Iranian COVID-19 patients. Methods: Five patients with confirmed COVID-19 who had acute respiratory distress syndrome and were supported by mechanical ventilation were treated with two consecutive PE containing fresh frozen plasma (FFP) of healthy donors and 0.9 % saline solution containing 5 % human albumin. Thereafter, CPT was performed just like PE, except that the FFP in this step was substituted with convalescent ABO-matched plasma. Clinical and laboratory factors were evaluated before and after treatments. Results: Three to Four patients showed lower body temperature and improved oxygen saturation as well as reduced laboratory factors such as c-reactive protein, lactate dehydrogenase, creatine phosphokinase (total and myocardial isoform), aspartate aminotransferase, blood urea nitrogen, bilirubin (total and direct), D-dimer, interleukin-6, and CD4+/CD8 + T cells ratio initially after PE and continued to improve so that they were discharged. One patient due to secondary hemophagocytic lymphohistiocytosis and extensive lung fungal infection was expired. Discussion: Overall, the PE followed by CPT was beneficial in reducing acute inflammation led to a considerable improvement in patients' clinical features. It seems that PE along with CPT could provide clearance of pro-inflammatory mediators as well as the positive effects of CPT. Controlled studies are required to confirm the effect of PE/CPT compared with other therapeutic approaches.